Operaciones de seriación y clasificación en niños de 5 años de instituciones educativas estatales y privadas - Callao - Torres Barrios, Rosario Marybel (2012)
The present study aimed to compare the development of cognitive structures operative classification and seriation among students in a state school with a private school of Callao. We evaluated a sample of 100 children whose average age was five. Test was applied for classification and seriation contained in the test battery FORCAB Operative, Training Cognitive-Affective Basic Structures. Reategui, Whose, Espinoza and Gutierrez (1977). The results showed differences between students from state school versus private only in the placement test, but not in the serialization for students of the private institution.